Risk Factors for Cervical Lymph Node Metastasis of Papillary Thyroid Microcarcinoma: A Single-Center Retrospective Study - Feng Cheng; Yanyan Chen; Lei Zhu; Bin Zhou; Yonghong Xu; Yiran Chen; Liping Wen; Shuzheng Chen (International Journal of Endocrinology)
Objective. To identify the clinicopathological features correlated to lymph node metastasis (LNM) in patients with papillary thyroid microcarcinoma (PTMC). Methods. Clinical data of 785 PTMC patients who underwent surgical treatment at the Lishui Municipal Central Hospital from September 2008 to December 2017 were retrospectively analyzed. Clinical and pathological risk factors for lymph node metastasis (LNM), central lymph node metastasis (CLNM), and lateral lymph node metastasis (LLNM) were analyzed. Results. LNM was found in 236 (30.2%) patients. Multivariate logistic regression analysis revealed that in PTMC, male gender, age<55 years, tumor size>5 mm, bilateral lesions, and extrathyroidal extension were independent risk factors for LNM in general and for CLNM. For LLNM, tumor size>5 mm, multifocal lesions, and extrathyroidal extension were independent risk factors. Conclusions. Identification of risk factors for cervical LNM could assist individualization of clinical management for PTMC.